Nuansa Kota Kolonial Surakarta Awal Abad XX: Fase Hilangnya Identitas Lokal - Susanto Susanto (Department of History, Faculty of Humanities, Diponegoro University, 2017)
This article examines changes Surakarta face in the early twentieth century. Surakarta was originally an Indis city, since the beginning of the century it progressed toward a colonial city. Based on the Dutch official reports in Surakarta, contemporary newspapers, and secondary sources, the city changes began with increasing number of Dutch female immigrants who came and settled at the city. They established nuclear families via marriage with fellow Dutchmen, so that the Dutch European community at Surakarta became stronger and more established. It was strengthened the government's confidence to intervene financial affairs in Javanese palaces and overhaul traditional structures by government reorganization and agrarian affairs. The government also implemented canonization policy in law, education, and culture. This policy was originally intended to implements European values in the Indies. However, in the policy development turned out to spawned a colonial society that was soon followed by the erosion of the city identity as Indis. The canonization policy also impacted on the changing patterns of intercommunity relations manifested in various discriminatory practices at various domains, that harassed and degraded the Indo community, especially the indigenous community. Both of them then rediscovered their identity order.